Polyethylene terephthalate‐polyethylene naphthalte copolymer films with high oxygen barrier properties via in‐situ polymerization with hydroxy‐terminated polybutadiene. Issue 11 (22nd September 2022) - Quan, Li‐Jun; Liu, Zhen‐Guo; Zhang, Qiu‐Yu; Li, Zhong‐Ming; Chen, Yan‐Hui
Abstract: A series of polyethylene terephthalate‐polyethylene naphthalate (PETN) copolymer films with excellent oxygen barrier properties were prepared by introducing trace amounts of hydroxy‐terminated polybutadiene (HTPB) into PETN via in‐situ polymerization. The PETN‐HTPB copolymer films had strong oxygen scavengering capability. Due to the reaction of HTPB with oxygen, highly dense oxidized layers were formed. The introduction of HTPB also enhanced the nucleation of the PETN and increased crystallinity. The stronger oxygen scavenging capacity, the formation of the oxidized layer, and the increased crystallinity together greatly improved the oxygen barrier performance of the PETN‐HTPB films. When the HTPB content was only 1.0 wt%, the oxygen permeability of the films was as low as 18.2 cc mil m −2 day −1 0.1 MPa −1, which was about 7.5 times lower than that of the pure PETN film. The maximum oxygen scavenging amount of the samples was 8.3 ml g −1 . The lowering of the diffusion coefficient instead of lowering of solubility was the main contributor to the decreasing permeability coefficient of the PETN‐HTPB films. This work provides a new idea for the preparation of high oxygen barrier polyester materials with oxygen scavenging capability. Abstract : Oxygen Barrier Properties and Mechanism of Oxygen‐absorbing polyethylene terephthalate ‐ polyethylene naphthalate copolymers